Sensitivity of test of significance - problem posed - Geary, R.C. (Economic & Social Studies, 1974)
This paper contains a preliminary examination of the effect of using the dichotomy (o, i ) instead of actual measurement in the study of relationship. First, the simplest case possible is dealt with, in the hope of inspiring, or provoking, more thorough treatment by others
Keywords: Mathematics; Regression